2018
DOI: 10.26710/jafee.v4i2.400
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Banking Sector Development on Capital Structure of Non-financial Sector Firms in Pakistan

Abstract: Objective: This study exemplifies how banking sector development influences capital structure of non-financial Sector firms. Methodology: In this study, deductive approach has been used and capital structure used as explained variable. Banking sector development used as explanatory variable and proxies by five key ratios. The six years data ranges from the year 2010 to 2015 used and fixed effect model applied for regression analysis. Findings: The statistical results indicate that first and 4th hypotheses part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…These proxies are well known and determined by The World Bank known as world development indicator (WDI) or macroeconomic factors 4 . Moreover, the previous studies have also considered these proxies as macroeconomic factors (Farooq et al, 2018; Konara & Wei, 2016; Mahmud, 2003; Onwe & Olarenwaju, 2014; Wuhan & Khurshid, 2015). Above of these, this study carried some firm‐specific variables, which may determine the corporate investment, that is, leverage (total debt to total asset), profitability (EBIT/total asset) and firm size (log of total sales).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These proxies are well known and determined by The World Bank known as world development indicator (WDI) or macroeconomic factors 4 . Moreover, the previous studies have also considered these proxies as macroeconomic factors (Farooq et al, 2018; Konara & Wei, 2016; Mahmud, 2003; Onwe & Olarenwaju, 2014; Wuhan & Khurshid, 2015). Above of these, this study carried some firm‐specific variables, which may determine the corporate investment, that is, leverage (total debt to total asset), profitability (EBIT/total asset) and firm size (log of total sales).…”
Section: Methodsmentioning
confidence: 99%
“…The sensitivity of corporate investment decision linked with both firm specific variables, that is, leverage (Bhagat, 2013; Mondosha & Majoni, 2018), firm size (Hamzah, 2017) and profitability (Pacheco, 2017) and macroeconomic conditions such as inflation rate (Onwe & Olarenwaju, 2014), interest rate (Wuhan & Khurshid, 2015) GDP growth rate, financial sector development (Khan et al, 2018) and foreign direct investment (FDI) (Konara & Wei, 2016). The literature is scarce on the effect of GDP growth rate, financial sector development and FDI on investment decision but other corporate factors showed the responsive behaviour towards GDP growth rate (Mahmud, 2003), financial sector development (Farooq, Ahmed, & Muhammad, 2018) and FDI (Marcin, 2008) which alternatively effect the corporate investment. The abundant literature had discussed the firm specific determinants but studies on macroeconomic variables found rare.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Specifically, this effect can be more pronounced in such economies that have less developed financial sector. This notion was also later supported by Farooq et al. (2018).…”
Section: Literature Reviewmentioning
confidence: 62%
“…Specifically, this effect can be more pronounced in such economies that have less developed financial sector. This notion was also later supported by Farooq et al (2018). Another empirical study conducted by Boissay and Gropp (2007) suggested the link between trade credit and firm performance.…”
Section: Literature Reviewmentioning
confidence: 79%
“…debt to equity ratio (total debt/total shareholder equity), debt to asset ratio (total debt/total assets), long-term debt to equity ratio (long term debt/total shareholder equity), and long term debt to assets ratio (long term debt/total assets ratio). The measurement of these variables was retrieved from previous studies published on same theme (Chakraborty, 2010;Farooq et al, 2018;Kayo, 2011). In addition to these variables, some other firm-specific variables i.e.…”
Section: Variables Of Studymentioning
confidence: 99%